A new generic name for the Cuban Bare-legged Owl Gymnoglaux lawrencii Sclater and Salvin - Olson, Storrs L.; Suárez, William (Zootaxa, 2008)
The two species of Antillean "screech" owls, notable for having unfeathered tarsi and lacking erectile "ear" tufts, have a rather complicated early history because specimens were at first very rare in collections so that for a long time no investigator was able to compare the two side by side.  The first to be described was Strix nudipes Daudin (1800), now known as the Puerto Rican Screech-Owl Otus nudipes (American Ornithologists' Union [AOU] 1983, 1998).   Bonaparte (1854) proposed the monotypic genus Gymnasio for the Puerto Rican bird with Strix nudipes Daudin as the type.